Rural Sanitation Market Expansion of Domestic Private Sector in Indonesia - World Bank (Washington, DC, 2015)
This report is a synthesis of fieldwork findings and recommendations developed since October 2012 under this Technical Assistance (TA) carried out by the World Bank’s Water and Sanitation Program (WSP). The recommendations have been developed through on-going consultations and meetings with the Directorate of Environmental Sanitation and Directorate General of Human Settlements, Ministry of Health, and Government of Indonesia. This report describes and assesses the performance of technical assistance TA-P143167, ‘rural sanitation market expansion of domestic private sector in Indonesia,’ provided by the World Bank through the Water and Sanitation Program (WSP) carried out from October 2, 2012 to March 31, 2015 to support the development of a rural sanitation market in Indonesia. This technical assistance (TA) was implemented as parts of a larger effort to assist the Government of Indonesia achieve at-scale results in rural sanitation through its National Strategy for Community-Based Total Sanitation (Sanitasi Total Berbasis Masyarakat - STBM).